Circadian regulation of Hepatitis B virus. - Forde, D (2020)
Whilst the role that circadian rhythm plays in human disease is emerging rapidly, its role in infection is only beginning to dawn. HBV affects over 350 million people globally with no cure and limited treatment options. Currently available interventions will not curb this epidemic. Every living organism on earth has evolved a circadian rhythm, whereby key systemic processes including metabolism, growth and immunity undergo seismic changes on a daily basis to maximise energy conservation. In order to achieve organism wide control, there are a myriad of individual cellular functions like autophagy that receive cues from a central pacemaker to optimise their functioning. The HBV replication cycle is known to be dependent on a competent autophagic pathway. It is unknown if HBV is being modulated by circadian rhythm and whether such overarching regulation would include autophagy as an intermediate process. The work presented here shows that the HepaRG cell line is permissive to HBV infection and is capable of sustaining an endogenous circadian rhythm. The NTCP receptor -key for HBV entry- is shown to be regulated by REV-ERBα. Separately, autophagosome maturation is shown to be delayed by HBV replication through the use of a dual fluorophore LC3 reporter. Both autophagy and HBV are shown for the first time to be pharmacologically modulated by an agonist of REV-ERB called SR9009, in addition to known autophagy regulators, thereby suggesting an intersecting point of governing pathways. I present evidence that HBV transcription, translation of HBsAg and HBeAg as well as mature virion release are susceptible to modulation by SR9009. Finally, I describe how an in vivo murine HBV model shows decreased HBV pgRNA and HBeAg following treatment with SR9009.